Adolescents with HIV and facial lipoatrophy: response to facial stimulation (Clinics, 2014)
OBJECTIVES: This study evaluated the effects of facial stimulation over the superficial muscles of the face in individuals with facial lipoatrophy associated with human immunodeficiency virus (HIV) and with no indication for treatment with polymethyl methacrylate. METHOD: The study sample comprised four adolescents of both genders ranging from 13 to 17 years in age. To participate in the study, the participants had to score six or less points on the Facial Lipoatrophy Index. The facial stimulation program used in our study consisted of 12 weekly 30-minute sessions during which individuals received therapy. The therapy consisted of intra- and extra-oral muscle contraction and stretching maneuvers of the zygomaticus major and minor and the masseter muscles. Pre- and post-treatment results were obtained using anthropometric static measurements of the face and the Facial Lipoatrophy Index. RESULTS: The results suggest that the therapeutic program effectively improved the volume of the buccinators. No significant differences were observed for the measurements of the medial portion of the face, the lateral portion of the face, the volume of the masseter muscle, or Facial Lipoatrophy Index scores. CONCLUSION: The results of our study suggest that facial maneuvers applied to the superficial muscles of the face of adolescents with facial lipoatrophy associated with HIV improved the facial area volume related to the buccinators muscles. We believe that our results will encourage future research with HIV patients, especially for patients who do not have the possibility of receiving an alternative aesthetic treatment.